4CPS-156 Analysis of the effectiveness and safety of daratumumab in monotherapy in adult patients with relapsed refractory multiple myeloma. (24th March 2020) - Alarcon-Payer, C; López López, AM; Gómez-De Rueda, F; Claramunt García, R; Barbero Hernández, MJ; Jiménez Morales, A
Abstract : Background and importance: Immunotherapy has broken new ground in the treatment of multiple myeloma, with the introduction of monoclonal antibodies into the therapeutic arsenal, representing a paradigm shift in treatment. Daratumumab is a human monoclonal antibody IgG1κ, which binds to the CD38 protein that is expressed at a high level on the surface of multiple myeloma tumour cells. Aim and objectives: To evaluate real life experience of daratumumab in monotherapy for the treatment of adult patients with relapsed refractory multiple myeloma (RRMM), who have previously received a proteasome inhibitor and an immunomodulatory agent and who have experienced disease progression since the last treatment. Material and methods: This was a multicentre, prospective, observational study, conducted over a period of 3 years in two third level hospitals, in 40 patients diagnosed with RRMM. To evaluate health outcomes, the following variables were measured: age, sex, number of previous lines, daratumumab cycles received, progression free survival (PFS) and adverse reactions. Results: Forty RRMM cases were analysed (80% men, 20% women). Mean age was 62 years. The health outcomes measured in our clinical practice were: 60% of patients received daratumumab as monotherapy, as thirdline treatment, 30% as fourthline treatment, and 10% as sixthline and seventhline treatment. The mean number of daratumab cycles was 7, except for one patient who has now completed cycle 27. Median PFS was 4 months. Only mild gastrointestinal adverse reactions (nausea and vomiting) were observed (20% of patients). The correct premedication was performed before and after daratumumab infusion, including 10 mg of oral montelukast (first infusion) and respecting the infusion times according to the technical datasheet. Conclusion and relevance: Health outcomes for daratumumab as monotherapy for the treatment of patients with RRMM were similar to those published in the combined trial gene 501 and SIRIUS. According to recent publications, daratumumab is likely to be more effective in combination with other drugs. Daratumumab is well tolerated in most patients and is therefore considered a safe treatment. References and/or acknowledgements: No conflict of interest.